2020
DOI: 10.1088/1757-899x/671/1/012113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incinerated and Non-Incinerated waste paper on Properties of Cement Mortar

Abstract: The cement industry is one of the most polluting industries globally, due to the high amount of CO2 emissions generated during production. Improving the sustainability of cement production is thus vital. Waste paper is also a big problem for many societies, especially in developed countries, where the use of board and paper increases almost every day. This work examines the possibility of using incinerated waste paper ash (IWPA) and non-incinerated waste paper (NIWP) as a partial replacement for cement (by wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The increase in the tensile strength of mortar samples containing WNP may be attributed to the improvement in adhesion performance between the rough surface of WNP and the cement paste [ 34 , 35 ]. However, in some samples that contain WNP, strength degraded due to the fiber ball phenomenon [ 33 ], indicating the need for further research on the correlation between the homogeneous dispersion method and mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the tensile strength of mortar samples containing WNP may be attributed to the improvement in adhesion performance between the rough surface of WNP and the cement paste [ 34 , 35 ]. However, in some samples that contain WNP, strength degraded due to the fiber ball phenomenon [ 33 ], indicating the need for further research on the correlation between the homogeneous dispersion method and mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the extensive usage of natural (fine and course) aggregate is one of the main reasons for the scarcity of natural aggregates in many countries around the world [4]. Furthermore, the cement industry consumes high energy as well as emits a high amount of CO2 into the atmosphere [5][6][7][8][9][10]. The cement industry contributes about 7% of carbon dioxide production worldwide [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Where previous work [28] has shown that the use of supplementary cementitious materials (SCM) can increase the service life of bridges in addition to reducing carbon dioxide emissions by reducing the cement content. Accordingly, the authors recommend investigating the effect of SCM such as fly ash, ground granulated blast furnace slag, metakaolin, silica fume, rice husks ash, waste paper, [29], [30], [39], [40], [31]- [38] and other SCMs [41]- [45] commonly used as substitutes for the cement to investigate their impact on the service life of bridges and thus including them in future structures. In addition to that, the use of industrial waste or by-products [33], [46], [55]- [59], [47]- [54] is considered a worthy topic in improving concrete technology in general from an environmental perspective and towards sustainability.…”
Section: Discussionmentioning
confidence: 99%